Pengembangan Permainan Ular Tangga Berbasis Komputer pada Materi Perpangkatan dan Bentuk Akar - Putri, Ade Yuni; Afgani, Muhammad Win; Paradesa, Retni (UNIVERSITAS RIAU KEPULAUAN, BATAM, INDONESIA, 2020)
The study was intended to produce a snake households computer based on any material and the power of valid form of the root, practical, and effective. Data collection techniques of the research is the survey, interview, and tests. A subject in this study is IX class of MTS Paradigma palembang. This is the kind of research research development with a groove ADDIE was ( Analyze, Design, Develop, Implementation, Evaluate ). Through the ADDIE was so this research result is obtained a snake computer based on any material the power of households and forms the root of which (1) valid based on comments and suggestions on how the game developed researchers and students have been given by validator (2) practical survey based on the practicality of 82 % students who have stated that the practical game households (3) effective virtue of 88 % survey and 83 % test the scores coming into categories is very effective.